The beginnings of Christology: a study in its problems. - Marxsen, Willi, 1919-1993 (Facet books. Biblical series, 22, 1969)
The Cambridge Companion to Proust, first published in 2001, aims to provide a broad account of the major features of Proust's A la recherche du temps perdu. Progressing from background and biographical material, the chapters investigate such essential areas as the composition of the novel, its social dimension, its intellectual parameters and its humour.